Do village allocation funds contribute towards alleviating hunger among the local community (SDG#2)? An insight from Indonesia - Elizabeth T. Manurung; Sylvia F. E. Maratno; Paulina Permatasari; Arif B. Rahman; Reifa Qisthi; Elvy M. Manurung (Economies, 2022)
Using an exclusive data set from Indonesia in 2018-2020, this study aims to prove whether there is a relationship between the allocation of village funds and the level of hunger in the community. In particular, this study tries to find out whether the Village Fund allocation policy has an effect on the achievement of the United Nations Sustainable Development Goal 2 (SDG#2). Using a quantitative method with regression analysis, this study found that the allocation of village funds by the Indonesian government supported hunger and poverty alleviation in all areas of Indonesia's villages. This research result has implications for policymaking on sustainable food inclusion, especially in Indonesian villages.
Keywords: 330; level of hunger; poverty and hunger pattern; SDG#2; village funds; zero hunger